Infrastructure in mobile opportunistic networks - Goswami A.; Gupta R.; Parashari G.S. (My University, 2025)
Opportunistic networks or OPNETs are challenged networks with sporadic communication opportunities and erratic link performance. OPNETs are simply considered complementary to traditional networks particularly at the time of disaster or at the locations without adequate network infrastructure. However, OPNETs are neither obsolete even after unprecedented infrastructural development in traditional networks nor ubiquitously deployed parallel to traditional networks. The need of the hour is to look at these networks with a newer vision considering current developed status of traditional networks. OPNETs can offer cellular network offloading, communication in challenged areas, proximity-based applications and censorship circumvention. This chapter will discuss the concept, protocol, architecture, cooperative framework, routing techniques, privacy issues and future directions of research in OPNETs. © Springer Nature Singapore Pte Ltd. 2018.